Vitamin D3 levels and NLRP3 expression in murine models of obese asthma: association with asthma outcomes - Zhang,J-H. (2018)
Vitamin D (25(OH)D3) is an essential nutrient that plays a role in the immune system. Serum 25(OH)D3 is found to be associated with asthma. However, the role of vitamin D in obese asthma remains unclear. Therefore, we investigated the association between vitamin D levels and asthma outcomes in a murine model of obese asthma. We also evaluated NLRP3 inflammasome activity in the pathogenesis of obese asthma. We divided 20 male Balb/c mice (3–4 weeks old) into 4 groups: normal control, asthma, obese, and obese asthma and developed an obese asthma mouse model. Airway hyperreactivity, cytokine concentrations, 25(OH)D3 levels, NLRP3 mRNA and IL-1β mRNA expressions were measured. Lung histology and bronchoalveolar lavage fluid (BALF) cell count were also determined. Obese asthma mice showed a significant increase in airway hyper-responsiveness, airway inflammation, pro-inflammatory cytokine levels and NLRP3 mRNA, IL-1β mRNA expression. Both asthma and obese groups had lower 25(OH)D3 levels. Vitamin D levels in obese asthma were the lowest among all groups. Vitamin D levels correlated negatively with body weight, lung resistance levels at 25 mg/mL of methacholine, total inflammatory cells, and IL-1β and IL-17 concentrations in BALF. These data demonstrated an association between serum vitamin D levels and outcomes of obese asthma, and indicated that NLRP3 inflammasome may play a role in this disorder.